DIMENSI DIMENSI SOSIO POLITIK ABU A’LA AL-MAUDUDI DALAM TAFHIM AL-QUR’AN - Nur Anis Rochmawati (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2022)
Almost all researchers categorize Abu A’la al-Maududi as the founder of Islamic politics in Pakistan. as other interpreters who find difficult to avoid subjectivity, Maududi’s interpretation of the Qur'an is also influenced by what he has been fighting for. Tafhi>m al-Qur'an is a work of interpretation that is full of socio-political dimensions and becomes a tool of legitimacy. Departing from this, this research will discuss aboutMaududi's thoughts on the socio-political problems that surround his region, Pakistan. Through the historical approach of thought, it will known how the concept of jihad and the Islamic state which has been a trend of renewal that he continues to encourage. A critical analysis was also presented by the researcher as a response to Maududi's interpretation model.